The usage of cosmetic product containing skin-lightening ingredients among female nursing students in Sabah, Malaysia - Deena Clare Thomas; Arlene C T; Emilia E; Noor Syaffa Shawani Y X H (Malaysian Journal of Medicine and Health Sciences, 2020)
Rooted form the ancient times, having a white and a delicate skin has been a dream of all women as it is perceived as a perfect beauty. Due to this high desideratum, the global beauty industry had taken an advantage to this target group promising an instant white skin for as early as three days. Global industry analysts (GIA) pre¬dicted that this year 2020 the global market for skin lighteners will reach $23 billion. Despite the effectiveness of using skin-lightening, some had reported of having adverse effect including dermatological as well as neurological. Methods: This is a quantitative study using descriptive analysis approach to all nursing students in Sabah. The type of sampling is using snowball sampling methods. A questionnaire was developed and distributed to all nursing colleges in Sabah. Results: A total of 161 nursing students responded. Based on this study, most of students start are using cos¬metic product in the age of15years old. Using an open-ended question, the top three cosmetic products containing skin-lightening ingredients use by students are Safi(27.9%), Garnier (25.5%)and Simple(16.1.%). Majority experience acne (47.5%) and skin irritation (18.8%)after using cosmetic products containing skin-lightening ingredients while 36.6% did not experience any skin problem. It is about80% concern about safety when choosing skin care contain skin-lightening ingredients,76.9% will make an effort to read leaflet provided prior to purchasing, 69.4% aware about the list of dangerous ingredients in choosing skin care contain skin-lightening ingredients, 78.1% aware about its side effect. Conclusion: The outcome of this preliminary study lead to the conclusion that nursing students in Sa¬bah are aware that using a cosmetic product contain skin-lightening ingredient is harmful for them.